The influence of health literacy on how preschool educators and parents perceive the continuous development of health competencies within the framework of sustainability: Lithuanian case - Daniuseviciute-Brazaite, Laura; Draudviliene, Lina (Frontiers in Public Health, 2025)
Preschool education is one of the most important priorities of modern educational policies and the basis of lifelong learning. Health-literate educators and parents are better equipped to instill sustainable health practices in young children. Therefore, it is important to examine health literacy and determine how preschool educators and parents perceive the continuous development of health competencies within the framework of sustainability. The quantitative survey results revealed the dominant levels of general health literacy among respondents: problematic (31.1% vs. 33.5%) and sufficient (39.8% vs. 43.3%) for parents and teachers, respectively. Parents’ attitudes toward the development of children’s health competence within the framework of sustainability in preschool showed that parents and educators understand that their role is one of the most important factors in strengthening children’s health competence. However, most respondents spend only 2 h being active with children on healthy lifestyles (61.5% vs. 55%) for parents and teachers, respectively. A moderate correlation was found between health literacy and the weekly time spent developing children’s health competencies (r = 0.526). In addition, educators and parents who always or very often focus on the development of children’s health competence seek to plan daily activities in a way that would enhance health promotion (r = 0.463). Within the framework of sustainability, this influence becomes even more pronounced as sustainable health education aims to instill long-lasting, holistic health practices that benefit individuals and communities over time.